Brown Stink Bug (Hemiptera: Pentatomidae) Damage to Seedling Corn and Impact on Grain Yield. Issue 2 (4th March 2021) - Bryant, Tim B; Babu, Arun; Reisig, Dominic D
Abstract: Brown stink bugs, Euschistus servus, are an important early-season pest of field corn in the southeastern United States. Feeding in the early stages of corn development can lead to a number of growth deformities and deficiencies and, ultimately, a reduction in yield. An observational and two experimentally manipulated trials were conducted in 2017 and 2018 to 1) determine optimal timing for assessing brown stink bug damage, 2) assess the level of damage from which yield compensation can occur, and 3) examine the relationship between brown stink bug density and early-season damage and yield. Fields were identified with infestations of brown stink bugs and a damage rating system for early stages of corn was established. Varying rates of brown stink bug densities were introduced using field cages and damage was assessed throughout the season. The density and duration of stink bug infestations were critical factors for damage potential, with each day of active feeding per plant resulting in a loss of 14 kg/ha in yield. The level of damage in early stages of corn was categorized into easily identifiable groups, with only the most severe damage leading to a reduction in yield. Moderate and minimal feeding damage did not result in yield loss. This study emphasizes the need for early and frequent scouting of corn to determine the risk of damage and yield loss from brown stink bugs. Results from this study can be used to help develop management programs for brown stink bugs in the early vegetative stages of field corn.